Implementation of Ambush Marketing in 10 Local Brands at “Paris Fashion Week 2022” Phenomena - Rahardjo, Rahmatika Ajeng (Universitas Ahmad Dahlan, 2023)
This research discusses how to apply ambush marketing to 10 local Indonesian brands in the “Paris Fashion Week 2022” phenomenon. This study argues that this phenomenon is part of ambush marketing, where 10 (ten) local Indonesian brands hold independent fashion shows in Paris on behalf of Paris Fashion Week 2022. The focus of the problem in this research is on how ambush marketing in this phenomenon is viewed from the business side, the communication side, the ethical and moral side, and the legal side. Of the 10 (ten) local brands, the ones that had the most attention are the ayam geprek and skincare brands. This study argues that ambush marketing generally occurs at major sporting events in the world, but this time it is something relatively new at fashion shows. This research uses a qualitative descriptive approach with a case study method. This method was carried out by observing and studying internet news regarding 10 (ten) local Indonesian brands appearing at the 2022 Paris Fashion Show. Data collection techniques were carried out by collecting references and data literature from various sources, such as books, journals, and the internet, related to ambush marketing. This study uses the concept of “ambush marketing” as an analytical tool to explain the practices carried out by 10 (ten) local Indonesian brands in ‘riding’ the Paris Fashion Week 2022 event. The urgency of this research is to add to the literature on ambush marketing in the Indonesian context, which is rarely discussed in communication studies.